Executive Committee Minutes 2013-12-05 - Academic Senate:::::::::
Agenda Approved. Minutes of 10/31 and 11/14 approved. Vice Chair's Report. Vice President of Administration and Finance Report. Resolution on a Gender and Sexuality Coordinator approved for the Senate agenda. Provost Report. Film Studies minor revision approved for Senate's consent calendar. EPC Report. FSAC Report. SAC Report. AMCS Curricular revisions approved for Senate's consent calendar. Naming Opportunity. Proposed change to the Course Outline Policy referred back to FSAC and SAC. SEIE Policy referred back to APC. Resolution for Andy Merrifield approved for Senate agenda. Senate Agenda approved.